Охорона пам’яток культури на Харківщині в роки революції та громадянської війни - Нестуля, О.О. (My University, 1995)
Nestulya A. A. Protection of Cuhural Monuments of Kharkov Region During the Years of Ukrainian Revolution and Civil War